2017
DOI: 10.1007/s13353-017-0396-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of genetic architectures for nine developmental traits of rye

Abstract: Genetic architectures of plant height, stem thickness, spike length, awn length, heading date, thousand-kernel weight, kernel length, leaf area and chlorophyll content were aligned on the DArT-based high-density map of the 541 × Ot1–3 RILs population of rye using the genes interaction assorting by divergent selection (GIABDS) method. Complex sets of QTL for particular traits contained 1–5 loci of the epistatic D class and 10–28 loci of the hypostatic, mostly R and E classes controlling traits variation through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…Enhancement of plant, spike and leaf growth by GAMYB is also possible at least as a pleiotropic effect of this potent regulatory gene. Our previous study [18] identified QTL for plant height, thousand-grain weight and awn length within map interval containing ScGAMYB, thus confirming results presented here. Further study of ScGAMYB polymorphisms using wider collection of genetic stocks should bring more information about functions of this gene in various aspects of plant development.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Enhancement of plant, spike and leaf growth by GAMYB is also possible at least as a pleiotropic effect of this potent regulatory gene. Our previous study [18] identified QTL for plant height, thousand-grain weight and awn length within map interval containing ScGAMYB, thus confirming results presented here. Further study of ScGAMYB polymorphisms using wider collection of genetic stocks should bring more information about functions of this gene in various aspects of plant development.…”
Section: Discussionsupporting
confidence: 90%
“…Functional polymorphisms in GAMYB gene may be an important factor affecting variation of αamylase activity (AA) and possibly other important traits of cereals. This possibility should be explored since wheat, barley and rye chromosome 3 was shown to contain a number of QTL for AA, preharvest sprouting (PHS) and plant height (PH) [14][15][16][17][18][19]. Till now neither ScGAMYB sequence, polymorphisms and map location nor its relationship with agronomic traits have been characterized in rye.…”
Section: Introductionmentioning
confidence: 99%
“…Backcrossing with cultivar components and selection for dwarfing alleles should clarify this problem. The chromosome 3RL region containing the Ddw4 locus is also a QTL localization place for thousand-kernel weight, kernel length, kernel thickness and kernel number per spike [ 5 ]. Close linkage between these QTL and the dwarfing gene may result in association of grain parameters with plant height, which means that allele compositions in these loci in a short-straw donor line is crucial for the agronomic performance of developed progenies.…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of the studied mapping populations, plant height shows quantitative variation controlled by complex networks of interacting quantitative loci (QTL), as revealed in rice [ 1 ], wheat [ 2 ], barley [ 3 4 ], and rye [ 5 7 ]. Because of the high number and small and/or unstable effects, QTL are usually ineffective tools for practical breeding.…”
Section: Introductionmentioning
confidence: 99%
“…There are more cases of similar QTL positions detected in other studies, that is PH on Chr. 1RS, 2RS, 2RL, 3RL and 5RS (Masojć, Milczarski, & Kruszona, 2017; Miedaner et al, 2012; Myśków, Hanek, Banek‐Tabor, Maciorowski, & Stojałowski, 2014). According to the literature collected at present, no QTL controlling PH in wheat, barley or other plants have been reported corresponding to the QTL of controlling PH in A. Gaertn.…”
Section: Discussionmentioning
confidence: 99%